Machine learning-based radiomic evaluation of treatment response prediction in glioblastoma. Issue 8 (August 2021) - Patel, M.; Zhan, J.; Natarajan, K.; Flintham, R.; Davies, N.; Sanghera, P.; Grist, J.; Duddalwar, V.; Peet, A.; Sawlani, V.
Abstract : AIM: To investigate machine learning based models combining clinical, radiomic, and molecular information to distinguish between early true progression (tPD) and pseudoprogression (psPD) in patients with glioblastoma. MATERIALS AND METHODS: A retrospective analysis was undertaken of 76 patients (46 tPD, 30 psPD) with early enhancing disease following chemoradiotherapy for glioblastoma. Outcome was determined on follow-up until 6 months post-chemoradiotherapy. Models comprised clinical characteristics, O 6 -methylguanine-DNA methyltransferase (MGMT) promoter methylation status, and 307 quantitative imaging features extracted from enhancing disease and perilesional oedema masks on early post-chemoradiotherapy contrast-enhanced T1-weighted imaging, T2-weighted imaging (T2WI), and apparent diffusion coefficient (ADC) maps. Feature selection was performed within bootstrapped cross-validated recursive feature elimination with a random forest algorithm. Naive Bayes five-fold cross-validation was used to validate the final model. RESULTS: Top selected features included age, MGMT promoter methylation status, two shape-based features from the enhancing disease mask, three radiomic features from the enhancing disease mask on ADC, and one radiomic feature from the perilesional oedema mask on T2WI. The final model had an area under the receiver operating characteristics curve (AUC) of 0.80, sensitivity 78.2%, specificity 66.7%, and accuracy of 73.7%. CONCLUSION: Incorporating a machine learning-based approach using quantitative radiomic features from standard-of-care magnetic resonance imaging (MRI), in combination with clinical characteristics and MGMT promoter methylation status has a complementary effect and improves model performance for early prediction of glioblastoma treatment response. Highlights: Early assessment of treatment response in glioblastoma is a key clinical issue. Contrast-enhanced MRI cannot differentiate early true- and pseudo-progression. Quantitative imaging-based radiomic features can be used as potential biomarkers. We used radiomic, clinical and molecular features in machine learning-based models. A combined clinico-radiomic model demonstrated the highest performance.